Negative factors that impede the development of transport in Ukraine - Chernyavskaya, T.A. (Економічний вісник Донбасу, 2010)
The comprehensive analysis of problems and develop the transport sector of Ukraine in the light of threats and risks including the crisis processes. Special attention is paid to achieve stabilization and optimization of functioning transport sector due to competitive advantages and potential opportunities. Key words: transport complex transport network, the transit potential of transportation operational condition.